2020
DOI: 10.4103/2045-9912.296038
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of molecular hydrogen increases breath acetone excretion during submaximal exercise: a randomized, single-blinded, placebo-controlled study

Abstract: Aerobic exercise is widely accepted as a beneficial option for reducing fat in humans. Recently, it has been suggested that molecular hydrogen (H 2 ) augments mitochondrial oxidative phosphorylation. Therefore, the hypothesis that inhaling H 2 could facilitate lipid metabolism during aerobic exercise was investigated in the current study by measuring the breath acetone levels, which could be used as non-invasive indicators of lipid metabolism. This study aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…In a double-blinded, placebo-controlled study, 4 weeks administration of hydrogenrich water (HRW) helped reduce and prevent accumulated oxidative stress in the brain, thereby improving mood, anxiety, and autonomic function in adult volunteers (Mizuno et al, 2017). Recently, several studies have arisen to explore the potential anti-fatigue effects of H 2 (Table 1) in healthy cohorts who performed either acute or chronic exercise, and shown the promise of intaking H 2 either before or after the exercise may help alleviate fatigue (Aoki et al, 2012;Da Ponte et al, 2018;Botek et al, 2019;LeBaron et al, 2019;Mikami et al, 2019;Dobashi et al, 2020;Hori et al, 2020;Shibayama et al, 2020;Timon Andrada et al, 2020;Dong et al, 2022). For example, intaking HRW before exercise has been shown to improve exercise-induced decline of muscle function (Aoki et al, 2012), and thus alleviate fatigue (Pantovic et al, 2016); and the inhalation of hydrogen-rich gas mixture after exercise can help attenuated the reduction in athletic performance (e.g., the height of countermovement jump) (Shibayama et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a double-blinded, placebo-controlled study, 4 weeks administration of hydrogenrich water (HRW) helped reduce and prevent accumulated oxidative stress in the brain, thereby improving mood, anxiety, and autonomic function in adult volunteers (Mizuno et al, 2017). Recently, several studies have arisen to explore the potential anti-fatigue effects of H 2 (Table 1) in healthy cohorts who performed either acute or chronic exercise, and shown the promise of intaking H 2 either before or after the exercise may help alleviate fatigue (Aoki et al, 2012;Da Ponte et al, 2018;Botek et al, 2019;LeBaron et al, 2019;Mikami et al, 2019;Dobashi et al, 2020;Hori et al, 2020;Shibayama et al, 2020;Timon Andrada et al, 2020;Dong et al, 2022). For example, intaking HRW before exercise has been shown to improve exercise-induced decline of muscle function (Aoki et al, 2012), and thus alleviate fatigue (Pantovic et al, 2016); and the inhalation of hydrogen-rich gas mixture after exercise can help attenuated the reduction in athletic performance (e.g., the height of countermovement jump) (Shibayama et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The included studies implemented three types of hydrogen, that is, hydrogen-rich water (HRW) ( n = 13) ( 23 26 , 28 , 30 , 41 – 47 ), hydrogen-rich gas (HRG) ( n = 3) ( 27 , 29 , 48 ), and hydrogen-rich calcium powder (HRC) ( n = 1) ( 49 ). Hydrogen concentrations varied considerably (e.g., HRW: 0.5~5.9 ppm; HRG: 1 to 68%) across these studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two exercise types (continuous and intermittent) were used to induce fatigue. Specifically, eight studies ( 23 , 25 28 , 41 , 45 , 49 ) used continuous load-incremental exercise (i.e., incremental treadmill running test, incremental cycling test); four studies ( 29 , 42 , 46 , 48 ) used continuous fixed-load exercise; one study ( 30 ) used a 4.2-km up-hill race; three studies ( 24 , 44 , 47 ) used intermittent sprint exercises; and the other one ( 43 ) used an intermittent judo fitness test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, clinical studies have revealed that breathing 1% H 2 for 20 min whilst exercising amplifies breath-acetate concentrations, a non-invasive marker of lipid metabolism, indicating that this application method promotes favorable lipid metabolism [86]. Similarly, 4% H 2 inhalation for 7 days improved running velocity and reduced levels of insulin-like growth factor-1 (IGF-1), a regulator of glucose transportation, in the bloodstream [87].…”
Section: Inhalation-h 2 and Hhomentioning
confidence: 94%